Sulfide intrusion in seagrasses assessed by stable sulfur isotopes—a synthesis of current results - Holmer, Marianne; Hasler-Sheetal, Harald (Frontiers in Marine Science, 2014)
Sulfide intrusion in seagrasses, as assessed by stable sulfur isotope signals, is widespread in all climate zones, where seagrasses are growing. Seagrasses can incorporate substantial amounts of 34S-depleted sulfide into their tissues with up to 87% of the total sulfur in leaves derived from sedimentary sulfide. Correlations between δ34S in leaves, rhizomes and roots show that sedimentary sulfide is entering through the roots, either in the form of sulfide or sulfate, and translocated to the rhizomes and the leaves. The total sulfur content of the seagrasses increases as the proportion of sedimentary sulfide in the plant increases, and accumulation of elemental sulfur (S0) inside the plant with δ34S values similar to the sedimentary sulfide suggests that S0 is an important reoxidation product of the sedimentary sulfide. The accumulation of S0 can, however, not account for the increase in sulfur in the tissue, and other sulfur containing compounds such as thiols, organic sulfur and sulfate contribute to the accumulated sulfur pool. Experimental studies with seagrasses exposed to environmental and biological stressors show decreasing δ34S in the tissues along with reduction in growth parameters, suggesting that sulfide intrusion can affect seagrass performance.